On-Chip mm-Wave Second-/Third-Order BPF and Balun With Wide Stopband and Low Radiation Loss Using SIDGS Resonators in 40-nm CMOS - Tang, Deshan; Luo, Xun (IEEE transactions on microwave theory and techniques, 2023)
In this article, two millimeter-wave substrate-integrated defected ground structure (SIDGS) resonators are proposed for filters and balun implementation. Such SIDGS resonators are composed of defected ground structure (DGS) with grounded shield and surrounding vias, which not only exhibit wide stopband with low radiation loss but also are flexible to integrate with active circuits. Using different coupling methods, second-/third-order bandpass filters (BPFs) and filtering balun are designed based on the proposed SIDGS resonators. The filters and balun are fabricated in a standard 40-nm complementary metal-oxide-semiconductor (CMOS) technology. The second-order filter is centered at 28 GHz with an insertion loss of the 2.7-and 3-dB FBW of 20.4%. Meanwhile, the stopband extends to 140 GHz with a rejection level of 30 dB. The third-order filter operates at 28 GHz with an insertion loss of the 2.9-and 3-dB FBW of 47%. Meanwhile, the stopband extends to 170 GHz with a rejection level of 27 dB. The filtering balun operating at 25 GHz with the 3-dB FBW of 32% exhibits in-band amplitude/phase imbalances of 0.6 dB and ± 1.1 ^° , respectively. The minimum in-band insertion loss is 2 dB excluding the theoretical 3-dB loss. The stopband extends to 175 GHz with a rejection level of 30 dB.